The Effect of Financial Performance Using the DuPont System on Stock Returns for Companies in the Energy Sector Listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 Period - Reinata Auliya Rachmandes; Achmad Fauzi; Dwi Handarini (Publikasi Indonesia, 2026)
This study examines the effect of financial performance, measured using the DuPont System—Net Profit Margin (NPM), Total Asset Turnover (TATO), Equity Multiplier (EM), and DuPont Return on Equity (DuPont ROE)—on the stock returns of energy-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period, with Signaling Theory serving as the theoretical framework. The study employs a quantitative approach involving a population of 89 energy-sector companies. Using purposive sampling, 68 companies comprising 204 firm-year observations were selected, with the final sample reduced to 195 observations after outlier treatment. Stock returns were calculated based on realized returns over an event window of five trading days before and five trading days after the publication date of the annual financial statements. Panel data regression analysis was performed using EViews 12, with the Common Effect Model (CEM) selected based on the Chow test and Lagrange Multiplier test results. The t-test results indicate that NPM, TATO, and EM have no statistically significant effect on stock returns, whereas DuPont ROE has a positive and statistically significant effect. The adjusted R² value of 6.03% indicates that the four variables explain only a small proportion of the variation in stock returns, while the remaining variation is attributable to other factors not included in the model, such as fluctuations in global energy commodity prices. These findings suggest that, when examined individually, the components of the DuPont System provide insufficient explanatory power regarding stock returns.